KEBUDAYAAN MASYARAKAT DI LINGKUNGAN JALAN NUSA INDAH RAYA MARINDAL 2 KAMPUNG BARU DUSUN 2 - Nurjannah; Annisa Natasya; Afat Zidane Padiska; Aslamul Huda; Devi Widiya; Nabila Syahfitri Zebua (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Culture is a conceptual tool for interpretation and analysis. Therefore, the existence of culture is crucial, as it supports discussions regarding the existence of a society. Culture, as a system of cultural activities and physical products of human beings within a society, emerges through learning processes, both formal and informal. This demonstrates that culture does not emerge spontaneously; rather, it exists because of the existence of humans within a social community, thus mutually supporting each other. Humans create culture as an effort to sustain life on this earth, because with culture, humans are able to carry out their duties on this earth as caliphs. Through culture, human religious life is also evident, and this distinguishes them from other types of creatures on this earth.